THE INFLUENCE OF AUDIT EXPERIENCE, ROLE AMBIGUITY, AND HEALTHY LIFESTYLE ON AUDITOR PERFORMANCE WITH SPIRITUAL INTELLIGENCE AS AN INTERVENING VARIABLE (STUDY ON KAP AT SURABAYA CITY) - Andari, Miranda Putrin; Hermawan, Sigit (Antis-Publisher, 2025)
Objective: Research was conducted to determine the influence of audit experience, role ambiguity, and healthy lifestyle on auditor performance with spiritual intelligence as an intervening variable (Study at KAP in Surabaya City). Method: In this study, the sample used was 65 KAP auditors in Surabaya. In this research, data analysis uses Partial Least Square (PLS). Results: The results obtained from this research are that audit experience, role ambiguity and healthy lifestyle partially influence auditor performance, using the t-test with a significant value of <0.05. Audit experience, role ambiguity, and healthy lifestyle partially influence spiritual intelligence, using the t-test with a significant value <0.05. Spiritual intelligence partially influences auditor performance, using the t-test with a significant value <0.05. Spiritual intelligence mediates audit experience, role ambiguity and healthy lifestyle using the t-test with a significant value <0.05. These results state that hypothesis testing can be accepted and proven to be true. Novelty: This study integrates spiritual intelligence as a mediating variable between audit experience, role ambiguity, and healthy lifestyle in relation to auditor performance, which adds a unique perspective to existing research in the auditing field, particularly in the context of public accounting firms in Surabaya.